A comparison of four typical green exercise environments and prediction of psychological health outcomes. (May 2016) - Rogerson, Mike; Brown, Daniel K; Sandercock, Gavin; Wooller, John-James; Barton, Jo
Aims: 'Green exercise' (GE) is physical activity while simultaneously being exposed to nature. GE comprises three physical components: the individual, the exercise and the environment, and one processes component encompassing a range of psychological and physiological processes. Previous research has consistently shown affective benefits of GE compared to equivalent non-GE. Investigating the possibility of optimum GE environments may help maximise health benefits. The aim of this study was to compare affective outcomes of GE participation between four different typical GE environments (beach, grasslands, riverside, heritage), and further examine influences of several physical component–related variables and one processes component–related variable, on these outcomes. Method: Participants ( N = 331) completed questionnaires before and after a 5km run, at one of four parkrun event locations. Results: Self-esteem (Δ = 1.61, 95% confidence interval (CI) = (1.30, 1.93)), stress (Δ = −2.36, 95% CI = (−3.01, −1.71)) and mood (Δ = −5.25, 95% CI = (−7.45, −3.05)) all significantly improved from pre- to post-run ( p < .05). Improvements in these measures were not significantly different between environments. Several component-related variables significantly predicted these improvements, accounting for 9% of self-esteem improvement, 1.6% of perceived stress improvement, and 9.5% of mood improvement. Conclusion: GE offers accessible provision for improving acute psychological wellbeing. Although nature-based exercise environments can facilitate affective outcomes, the overall type of nature may be less critical. Other characteristics of the individual, exercise and environment can significantly influence attainment of psychological GE benefits. However, the results support a greater importance of the processes component in attaining previously reported affective outcomes.